PEMANFAATAN VIDEO DALAM BERDAKWAH (STUDI METODE DAKWAH UAS) - Mahmuddin Mahmuddin; Kusnadi Kusnadi (Fakultas Dakwah dan Komunikasi, 2021)
This study aims to determine the da'wah method of Ustads Abdul Somad (UAS) in preaching and to find out the advantages and disadvantages of UAS in preaching through video and to find out the da'wah models developed by UAS in preaching in video media. The method used is content analysis in videos found on YouTube. The results showed that the UAS da'wah method was the da'wah method of al-hikmah, mauidzah and billati hiya ahsan. The advantages of UAS video lectures are: light lecture material, easy to understand delivery, use of language that is easily understood by all people, light jokes, precise arguments, use of gestures that match what he says, loud, loud and clear voice. firmly with the right intonation and with good rhetoric. the drawback is that the uploaded lecture video does not include a question and answer session, there is no subtitle, the accent is thick with a Sumatran accent, a lot of the videos are cut off. The UAS da'wah model is transformative, actual, cultural